Health-related quality of life in patients with systemic sclerosis: evolution over time and main determinants - van Leeuwen, Nina M (Rheumatology (Oxford), 2021)
OBJECTIVES: In SSc patients, disease specific determinants that influence health-related quality of life (HRQoL) over time have not been described. We aim to, in patients with SSc, (i) evaluate if and how HRQoL changes over time, and (ii) assess how different SSc domains and functional impairments contribute to changes in HRQoL over time. METHODS: All SSc patients from the Leiden SSc cohort were included; patients with disease duration <24 months were classified as incident cases. HRQoL was assessed prospectively on an annual basis using the EQ-5D and the SF36. To assess baseline associations between clinical characteristics and HRQoL, linear regressions were performed. To identify possible associations between SSc characteristics and HRQoL change over time, linear mixed models were performed in both incident and prevalent cases. RESULTS: In total, 492 SSc patients were included (n = 202 incident cases), with a median follow-up duration of 3.4 years. At baseline, presence of organ involvement was independently associated with a worse SF36 physical component score and lower EQ-5D score. Over time, gastrointestinal symptoms, Raynaud and digital ulcers were independently associated with deterioration of HRQoL in both incident and prevalent cases. In prevalent cases, pulmonary arterial hypertension (PAH) was associated with a decrease in HRQoL over time. Worse functioning as measured by six-min walking distance, mouth-opening, finger-to-palm distance and grip-strength contributed significantly to deterioration of HRQoL over time. CONCLUSION: In SSc, key clinical burdens that contribute to worsening of HRQoL over time include digital ulcers, Raynaud and gastrointestinal involvement. In addition, PAH is a significant burden in prevalent disease.